2016
DOI: 10.1186/s40478-016-0287-6
|View full text |Cite
|
Sign up to set email alerts
|

Adamantinomatous and papillary craniopharyngiomas are characterized by distinct epigenomic as well as mutational and transcriptomic profiles

Abstract: Introduction: Craniopharyngiomas (CP) are rare epithelial tumors of the sellar region. Two subtypes, adamantinomatous (adaCP) and papillary CP (papCP), were previously identified based on histomorphological and epidemiological aspects. Recent data indicates that both variants are defined by specific genetic alterations, and influenced by distinct molecular pathways and particular origins. The fact that CP is an uncommon tumor entity renders studies on large cohorts difficult and exceptional. In order to achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 49 publications
8
116
1
4
Order By: Relevance
“…19 An additional 18 ACP samples underwent expression array analysis and were compared with 10 PCP samples by Holsken et al in 2016. 23 This study also highlighted the activation of the WNT and SHH pathways in ACP. In this paper, the methylation profiles of 25 ACPs and 18 PCPs were assessed, revealing distinct patterns between tumor types.…”
Section: Gene Expression and Methylation Analyses Of Acpmentioning
confidence: 97%
See 2 more Smart Citations
“…19 An additional 18 ACP samples underwent expression array analysis and were compared with 10 PCP samples by Holsken et al in 2016. 23 This study also highlighted the activation of the WNT and SHH pathways in ACP. In this paper, the methylation profiles of 25 ACPs and 18 PCPs were assessed, revealing distinct patterns between tumor types.…”
Section: Gene Expression and Methylation Analyses Of Acpmentioning
confidence: 97%
“…23,31 With respect to genomic copy number alterations, previous studies using G banding or comparative genomic hybridization have given variable, often controversial, results. While the majority showed normal karyotype, cases with copy number variants were described in some cohorts.…”
Section: Genetic Changes In Acpmentioning
confidence: 99%
See 1 more Smart Citation
“…Hölsken and colleagues 25 demonstrated a much higher expression of SHH pathway genes in the transcriptomes of ACP compared with PCP. These findings correlated with distinct methylation patterns between the 2 tumor types.…”
Section: 35mentioning
confidence: 99%
“…Genetic and molecular pathologic features support a distinct pathogenesis of aCP and pCP [1217]. It was reported that pCPs present BRAF p.V600E mutations in 95% of cases and CTNNB1 mutations are exclusive and specific to aCPs [16].…”
Section: Introductionmentioning
confidence: 99%